IDENTIFIKASI DAYA TARIK WISATA DI PANTAI KETAPANG RUPAT KABUPATEN BENGKALIS - ,, Nurhidayati; Martina, Elti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study is motivated by the importance of comprehensively identifying the components of tourist attractions at Ketapang Beach, Rupat District, Bengkalis Regency, in line with efforts to develop a sustainable tourism destination. The study aims to analyze the tourist attractions as well as the obstacles in their management. The method used is qualitative descriptive through observation, interviews, and documentation, with data analysis involving data reduction, presentation, and conclusion drawing. The results indicate that Ketapang Beach has strong and multidimensional tourist attractions, formed by a combination of recreational activities, natural beauty, and local cultural attractions. Tourist activities, including recreation, education, and social activities, demonstrate that the beach functions not only as a leisure space but also as a site for social interaction and learning. The natural uniqueness, such as the wide stretches of white sand, long coastline, coastal pine trees, and the view of the hills along the Rupat Island–Malaysia border, provides visitors with distinctive visual and emotional experiences. However, the management of Ketapang Beach’s tourist attractions still faces significant challenges, including limited funding, coastal abrasion, inadequate promotion, overlapping institutional responsibilities, insufficient facilities, and suboptimal accessibility. These conditions affect the maintenance of facilities, the development of attractions, and the overall sustainability of the beach’s tourism potential Keywords: tourist attractions, tourist activities, destination management, Ketapang Beach.